Factors Affecting the Accountability of Village Fund Management through the Implementation of the Village Financial System (Siskeudes) in Several Villages in Jatipurno District, Wonogiri Regency - Galuh Putri Ayunita Cahayani; Susilaningtyas Budiana Kurniawati; Supartini Supartini (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
The implementation of the Village Financial System (Siskeudes) in the management of village funds in Jatipurno Village, Wonogiri Regency, plays an important role in increasing the accountability and transparency of the use of the village budget. This system allows village officials to manage finances in a more structured manner, reduce the potential for errors in record-keeping, and make it easier to report finances to the community and local governments. This study aims to analyze the factors that affect the accountability of village fund management through the implementation of the Village Financial System (Siskeudes) in several villages in Jatipurno District, Wonogiri Regency. Siskeudes is expected to increase transparency and accountability in the management of village funds. However, this study found several obstacles faced in its implementation, including limited human resources, inadequate technological infrastructure, and lack of support from local governments. This research is expected to provide recommendations to increase the effectiveness of the implementation of Siskeudes in the management of village funds in the future.